Power Transformer Asset Management - Pracana Case Study - Miguel Sérgio Vieira Correia Soares (2017)
The power transformers comprise a great investment. The owners of this type of asset have a growing demand to extend the life of their transformer fleets. In this work, an analysis of the asset management and associated norms is made. In addition, power transformers are analyzed and their key parameters as well as the existing monitoring techniques and systems. A comparative analysis is made between health index calculation models that allow the evaluation of the condition of a power transformer. A health index is a tool that processes information by creating a score that describes the condition of an asset. Through this index it is possible to objectively determine the condition of power transformers in order to make maintenance or reinvestment decisions. Thus, it is possible to detect possible risk assets preventing them from failing, allowing an increase in the life time. The transformer to be analysed was a transformer that was in the substation of Pracana. Due to a network rearrangement at the end of 2007, this substation has become redundant. The substation was feeding a 60 kV network through a 63 MVA, shell type power transformer (150/63/10 kV). This was considered a unique case in Portugal, since power transformers are only available for this type of assessment, when a catastrophic failure occurs, preventing an analysis of ageing, since the areas of interest are damaged. Given the reasons that led to a controlled scrapping in this transformer, it was possible to collect a set of data that allowed the condition analysis, which focused mainly on the thermal degradation of insulation materials. Using the data collected during its operating time, as well as the data collected for the analysis of the thermal degradation of insulation materials, it is possible to apply health index calculation models. Methods of evaluating the condition of the transformer were used to make a comparison between them. These models will evaluate different subsystems of the transformer culminating in a final result that will indicate the general condition of the transformer.